Extratropical cyclones over the North Atlantic and Western Europe during the Last Glacial Maximum and implications for proxy interpretation - Pinto, Joaquim G.; Ludwig, Patrick (2020)
Extratropical cyclones are a dominant feature of the midlatitudes, as their passage is associated with strong winds, precipitation and temperature changes. The statistics and characteristics of extratropical cyclones over the North Atlantic region exhibit some fundamental differences between pre-industrial (PI) and Last Glacial Maximum (LGM) climate conditions. Here, the statistics are analysed based on results of a tracking algorithm applied to global PI and LGM climate simulations. During the LGM, both the number and the intensity of detected cyclones were higher compared to PI. In particular, increased cyclone track activity is detected close to the Laurentide ice sheet and over central Europe. To determine changes in cyclone characteristics, the top 30 extreme storm events for PI and LGM have been simulated with a regional climate model and high resolution (12.5 km grid spacing) over the eastern North Atlantic and western Europe. Results show that LGM extreme cyclones were characterised by weaker precipitation, enhanced frontal temperature gradients and stronger wind speeds than PI analogues. These results are in line with the view of a colder and drier Europe, characterised by little vegetation and affected by frequent dust storms, leading to reallocation and build-up of thick loess deposits in ...